New Perspectives on Innovative Drug Discovery: An Overview - Si Yuan Pan; Shan Pan; Zhi-Ling Yu; Dik-Lung Ma; Si-Bao Chen; Wang-Fun Fong; Yi-Fan Han; Kam-Ming Ko (Frontiers Media S.A., 2010)
Despite advances in technology, drug discovery is still a lengthy, expensive, difficult, and inefficient process, with a low rate of success. Today, advances in biomedical science have brought about great strides in therapeutic interventions for a wide spectrum of diseases. The advent of biochemical techniques and cutting-edge bio/chemical technologies has made available a plethora of practical approaches to drug screening and design. In 2010, the total sales of the global pharmaceutical market will reach 600 billion US dollars and expand to over 975 billion dollars by 2013. The aim of this review is to summarize available information on contemporary approaches and strategies in the discovery of novel therapeutic agents, especially from the complementary and alternative medicines, including natural products and traditional remedies such as Chinese herbal medicine.